In vitro culture of Piper attenuatum Ham. (Piperaceae): Callus induction and plant regeneration - SANDHYA, K MADHUSUDHANAN, B A RAHIMAN, B (Journal of Spices and Aromatic Crops, 1996)
Callus induction and plant regeneration of Piper attenuatum was achieved from stem explants in Murashige and Skoog and Gamborg’s basal media supplemented with 2,4-dichlorophenoxyacetic acid, indole-3-acetic acid, Kinetin, benzyladenine and palmyarh (Borassus flabelliferl endosperm extract. Root induction was obtained from stem explants in Murashige and Skoog medium supplemented with a-naphthaleneacetic acid, b-naphthoxyacetic acid, indole-3-acetic acid, benzyladenine, kinetin and coconut water. Shoot development was achieved in in vitro rooted stem segments planted in Murashige and Skoog’s medium supplemented with indole-3-acetic acid, benzyladenine and also in indole-3-acetic acid and kinetin. The plantlets were successfully established in soil. This is the first report of in vitro culture of P. attenuatum.